0340 Regional Changes in Sleep Electroencephalography Power in Youth with Sleep-Disordered Breathing: A High-Density EEG Study. (27th May 2020) - Myers, A; Matthews, C; Kille, T; Riedner, B; Flaherty, B; Jones, S
Abstract: Introduction: Daytime neurobehavioral impairments are commonly associated with sleep disordered breathing (SDB) in children. However, a large number of studies have shown only minimal differences in sleep between children with SDB relative to control children, suggesting that sleep dysfunction is not responsible for daytime impairment. Importantly, however, previous studies have measured sleep EEG using only frontal scalp electrodes, failing to capture the regional features of sleep that are prominent during development. Here we measure sleep using hdEEG in SDB and healthy children to determine if regional sleep impairment is related to daytime neurobehavioral performance. Methods: Overnight high-density electroencephalography (hdEEG, 256 channels) was recorded in 17 children with sleep disordered breathing (SDB) (age: M = 8.46, SD = 1.82, AHI: M = 11.3, SD = 8.6, 53% female) and 17 age and sex matched controls (age: M = 8.47, SD = 1.66, AHI: M = 1.5, SD = .64). Attentional capacity was assessed using the Test of Variables of Attention (TOVA) before and after sleep. Group differences in sleep macrostructure variables were assessed using unpaired t-tests. All-night spectral analysis was performed for NREM sleep and averaged across groups. Topographic differences between groups were assessed using statistical non-parametric mapping. Pearson correlations were used to determine associations between sleep and TOVA variables. Results: Sleep macrostructure did not differ between groups. All-night spectral density analysis revealed a global increase in high-frequency activity in N2N3 and N3, in the alpha band (8-12 Hz, p<0.05). Global alpha power was higher in SDB youth, although this effect reached significance during N3 in a large cluster of posterior channels ( N =55, p =.02). Conclusion: Elevated alpha during NREM is frequently considered a correlate of nonrestorative sleep. In this sample of youth with SDB, posterior alpha is robustly increased during the deepest stage of NREM sleep. In this small sample, however, alpha power did not predict performance on an attentional task sensitive to the effects of impaired sleep. Support: R21 HD092986-02 to SJ